Exhausted bodies and precious products: women's work in a Special Economic Zone for the electronics industry in Poland. (1st October 2012) - ,
Abstract : This article presents case study research conducted by participant observation in an electronics assembly plant based in one of the Special Economic Zones (SEZs) in Poland. The study was part of a broader research project on women workers' lives and SEZs development run by Feminist Think Tank, during which the author was author was employed as a temporary worker and worked on the production line for three months, from October to December 2011, during a production peak in the zone. Embedded in the context of industrial and labour market changes over the last decade, the case study illustrates the interrelated processes of neoliberal economic restructuring, development of SEZs and their consequences for women workers' lives in one Polish region.